2016
DOI: 10.1007/s13197-016-2396-4
|View full text |Cite
|
Sign up to set email alerts
|

Bread formulated with guava powder was enriched in phenolic and aroma compounds, and was highly acceptable by consumers

Abstract: Guava powder (GP) was used as source of aroma and phenolic compounds to fortify wheat bread 10% (GB10) and 20% (GB20), substituting for wheat flour. Phenolic compounds, antioxidant capacity, volatile compounds profile, and sensory acceptability of control bread (CB; without GP) and guava breads (GB) were evaluated. Incorporation of GP increased roughly 2-to-3-fold the phenolic compounds contents of bread. Ten phenolic compounds were identified in GB20, and quercetin-3-Orutinoside was the major compound, while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The addition of JPSP resulted in a 67% increase in total phenolic content in JB (267.3 mg/100 g) compared to CB (160.3 mg/100 g). Similarly, several studies have reported increased phenolic content in baking products incorporated with fruit powders (Ho et al ., 2013; Hayta et al ., 2014; Alves & Perrone, 2015; Arun et al ., 2015; Platat et al ., 2015; Bhol et al ., 2016; Castelo‐Branco et al ., 2016; Bourekoua et al ., 2018; Abreu et al ., 2019). Bioprocessing, however, only affects the total phenolic content in jabuticaba bread, leading to a 28% increase in JBB (341.8 mg/100 g) compared to JB (267.3 mg/100 g).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The addition of JPSP resulted in a 67% increase in total phenolic content in JB (267.3 mg/100 g) compared to CB (160.3 mg/100 g). Similarly, several studies have reported increased phenolic content in baking products incorporated with fruit powders (Ho et al ., 2013; Hayta et al ., 2014; Alves & Perrone, 2015; Arun et al ., 2015; Platat et al ., 2015; Bhol et al ., 2016; Castelo‐Branco et al ., 2016; Bourekoua et al ., 2018; Abreu et al ., 2019). Bioprocessing, however, only affects the total phenolic content in jabuticaba bread, leading to a 28% increase in JBB (341.8 mg/100 g) compared to JB (267.3 mg/100 g).…”
Section: Resultsmentioning
confidence: 99%
“…Control bread (CB) was prepared according to Castelo‐Branco et al . (2016) with modifications, in duplicate, in an automatic bakery machine (MultiPane, Britania®, Curitiba, Brazil) under conditions pre‐established by the manufacturer. The bread‐making process consisted of three stages: mixing (27 min at 28 °C), fermentation (130 min at 39 °C), and baking (60 min at 164 °C).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation